2018
DOI: 10.1165/rcmb.2017-0206rc
|View full text |Cite
|
Sign up to set email alerts
|

Maternal E-Cigarette Exposure in Mice Alters DNA Methylation and Lung Cytokine Expression in Offspring

Abstract: E-cigarette usage is increasing, especially among the young, with both the general population and physicians perceiving them as a safe alternative to tobacco smoking. Worryingly, e-cigarettes are commonly used by pregnant women. As nicotine is known to adversely affect children in utero, we hypothesized that nicotine delivered via e-cigarettes would negatively affect lung development. To test this, we developed a mouse model of maternal e-vapor (nicotine and nicotine-free) exposure and investigated the impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
141
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(164 citation statements)
references
References 33 publications
14
141
0
9
Order By: Relevance
“…A prior report showed that both 3 days and 4 weeks e‐cig exposure did not alter lung levels of IL‐1β, TNFα, and IL‐6 . In another report of a mouse model, lungs of mothers exposed to e‐cig aerosols with and without nicotine (18 mg/mL) showed increased protein levels of pro‐inflammatory cytokines IL‐1β, IL‐6 and TNFα . These findings are in agreement with our prior studies which demonstrated that a three days e‐cig (16 mg/mL nicotine) exposure caused a significant increase in pro‐inflammatory cytokines (IL‐1α, IL‐6, IL‐13, and MCP‐1) in BALF .…”
Section: Discussionsupporting
confidence: 91%
“…A prior report showed that both 3 days and 4 weeks e‐cig exposure did not alter lung levels of IL‐1β, TNFα, and IL‐6 . In another report of a mouse model, lungs of mothers exposed to e‐cig aerosols with and without nicotine (18 mg/mL) showed increased protein levels of pro‐inflammatory cytokines IL‐1β, IL‐6 and TNFα . These findings are in agreement with our prior studies which demonstrated that a three days e‐cig (16 mg/mL nicotine) exposure caused a significant increase in pro‐inflammatory cytokines (IL‐1α, IL‐6, IL‐13, and MCP‐1) in BALF .…”
Section: Discussionsupporting
confidence: 91%
“…A review of extant in vivo and in vitro studies relevant to vaping and pregnancy outcomes offers reason for concern and evidence for the necessity to pursue investigations into the effects of e‐cigarette aerosol inhalation on embryonic/fetal development. Analyses of offspring birth weight subsequent to exposure of pregnant mice to nicotine‐containing e‐vapors have failed to show reduced offspring birth weight compared to those from sham exposed and e‐vapor exposed dams (Chen, Li, Chan, et al, ; Lauterstein et al, ). Confirmation of this outcome in humans, however, is particularly important since the most well documented adverse outcome of exposure to tobacco smoke during pregnancy is infant low birth weight (Harrod et al, ).…”
Section: Are Ends a “Safer Alternative” To Tobacco Smoking During Prementioning
confidence: 99%
“…Now it is quite clear that certain flavoured e‐fluids can be toxic and e‐vaping harms not only the lung but also the other organs . Growing evidence from animal studies including those from our own group has suggested that e‐vaping during pregnancy may have detrimental impacts on multiple organ systems in the offspring at different postnatal ages, including the brain . Against the traditional beliefs, the adverse impact of maternal e‐cigarette vapour exposure on the offspring seems to be nicotine independent, suggesting noxious chemicals generated from the heated solvent may play a major role in the adverse impact on the health outcome in the offspring.…”
Section: Is Nicotine the Key Player?mentioning
confidence: 98%
“…[48][49][50] Growing evidence from animal studies including those from our own group has suggested that e-vaping during pregnancy may have detrimental impacts on multiple organ systems in the offspring at different postnatal ages, including the brain. [51][52][53][54][55] Against the traditional beliefs, the adverse impact of maternal e-cigarette vapour exposure on the offspring seems to be nicotine independent, suggesting noxious chemicals generated from the heated solvent may play a major role in the adverse impact on the health outcome in the offspring. For more detailed comparison between cigarette smoke and e-vapour exposure, please see the review by Li et al 56 Nevertheless, it can be concluded that e-cigarettes should not be used to during pregnancy.…”
Section: Is Ni Cotine the K E Y Pl Ayer?mentioning
confidence: 99%